Three Worlds in One: Venus as a Natural Laboratory for the Effect of Rotation Period on Atmospheric Circulation - Maureen Cohen; James Holmes; Stephen Lewis; Manish Patel; Sébastien Lebonnois (The Astrophysical Journal Letters)
Because of its rotation period of 243 days, Venus is considered a slowly rotating planet. However, its persistent superrotating atmospheric jets, which increase in speed from surface to cloud tops, effectively set a faster rotation speed than the surface rotation. Using the Venus Planetary Climate Model and wind measurements taken by the Pioneer Venus entry probes, we show that the Rossby radius of deformation of the atmosphere varies with height. The atmosphere falls into three circulation regimes: (1) from the surface to 20 km, the Rossby radius of deformation exceeds the planetary radius and no Rossby waves form; (2) from 20 to 50 km, the tropical Rossby radius becomes smaller than the planetary radius, and a circulation regime characterized by a superrotating equatorial jet and mid-latitude Rossby gyres appears; (3) from 50 to 70 km, the extratropical Rossby radius becomes smaller than the planetary radius, the jet develops mid-latitude maxima, and the Rossby gyres shift to high latitudes. Studies of exoplanetary circulation regimes as a function of rotation period have repeatedly shown a similar progression. While observing the circulations of exoplanets to confirm these predictions is not currently possible, the presence of different circulation regimes on Venus and their dependence on altitude could be tested by observing campaigns. Such evidence would be the first observational support for the theory connecting differences in planetary rotation periods to circulation regime transitions and would ground predictions of exoplanet circulations in a validated framework.